The Linked Exchange Rate System and FinTech Development: Synergistic Evolution of Hong Kong’s International Financial Centre Status - Xu, Ziyi (Transactions on Economics, Business and Management Research, 2026)
As a leading global international financial centre, Hong Kong’s financial system is anchored by the Linked Exchange Rate System (LERS) established in 1983. Characterized by 100% US dollar reserve backing and the Convertibility Zone of 7.75 to 7.85 Hong Kong dollars per US dollar, this system has provided monetary and financial stability for Hong Kong for over four decades. Concurrently, in response to the global digital economy wave, Hong Kong has accelerated its FinTech development in recent years—from the "FinTech 2025" strategy to the newly announced "FinTech 2030" blueprint—aiming to build next-generation data and payment infrastructure and promote financial tokenization. This paper examines the synergistic relationship between the traditional institutional cornerstone of LERS and the emerging developmental impetus of FinTech innovation. The study finds that the exchange rate stability and free capital movement provided by LERS create an ideal experimental environment for FinTech development; conversely, FinTech innovations such as central bank digital currencies (CBDC) and tokenized deposits hold the potential to optimize the operational efficiency of LERS and enhance its resilience in addressing future challenges. The synergistic evolution of these two pillars jointly consolidates and elevates Hong Kong’s status as an international financial centre.